Fanny McBride - Cookson, Catherine <1906-1998> (London : Corgi Books, 1983)
Now that her brood had left the nest, Fanny McBride, a large, cheerful and indomitable Tyneside widow, had time to sit by her window and watch the goings-on outside. There was plenty to keep her occupied: the mystery of the new woman at Mulhattanʻs Hall, the tenement block (here a fortnight already and not so much as a hello); the long-standing feud with Mrs Flannagan over the street; after-school visits from her grandson Corny, cheeky as a sparrow with an appetite like a gannet. Not that Fanny had any intention of ending her days in lonely isolation, however. And so when her friend Mary fell sick and had to give up work for a few weeks, it was Fanny who took her place. It tickled her to think how her son Phil would react. After all, he was the clever one, a clean collar every day for his job in the Borough Treasurer's office. She could just picture his face when she told him sheʻd got a job in town - looking after the ladies' lavatories
Zweigstelle: Patientenbücherei Haupthaus
Exemplar/Standort: Engl Cook (PatBü)
Exemplar/Standort: Patientenbücherei Haupthaus
Text in engl. Sprache
Keywords: Englisch; Fremdsprachiger Text